2023
DOI: 10.3390/plants12193360
|View full text |Cite
|
Sign up to set email alerts
|

Citrus Pruning in the Mediterranean Climate: A Review

Pedro Matias,
Isabel Barrote,
Gonçalo Azinheira
et al.

Abstract: Pruning is a common practice in citrus for various reasons. These include controlling and shaping the canopy; improving phytosanitary health, productivity, and fruit quality; and facilitating operations such as harvesting and phytosanitary treatments. Because pruning is an expensive operation, its need is sometimes questioned. However, it has been proven to be particularly important in Mediterranean citriculture, which is oriented towards producing fruits for a high-quality demanding fresh market. Herein, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 103 publications
0
4
0
1
Order By: Relevance
“…Matias et al demonstrated that pruning is an effective method for controlling the development and shape of citrus trees (Citrus reticulata Blanco), improving fruit quality and yield, promoting pest and disease control, reducing production costs, and decreasing alternate fruiting. It can be seen that the study provides objective evidence for the benefits of pruning in citrus tree cultivation [26]. Another research from Song et al has studied the effect of pruning to improve fruit yield and quality in densely planted 'Red Fuji' apple (Malus pumila Mill.)…”
Section: Discussionmentioning
confidence: 91%
“…Matias et al demonstrated that pruning is an effective method for controlling the development and shape of citrus trees (Citrus reticulata Blanco), improving fruit quality and yield, promoting pest and disease control, reducing production costs, and decreasing alternate fruiting. It can be seen that the study provides objective evidence for the benefits of pruning in citrus tree cultivation [26]. Another research from Song et al has studied the effect of pruning to improve fruit yield and quality in densely planted 'Red Fuji' apple (Malus pumila Mill.)…”
Section: Discussionmentioning
confidence: 91%
“…The development of new shoots usually coincides with new aphid infestations [5,49] and consequently with aphids' damage. Therefore, cultural practices, such as citrus pruning and the resulting onset of new shoots, must be used with great care and discernment, in particular when climatic conditions are favorable to the development of aphid vectors.…”
Section: Discussionmentioning
confidence: 99%
“…For a given aphid species, injury depends on the ecological characteristics of the agricultural system, which, in addition to regional climatic conditions, is very dependent on human activities. The plant (citrus host species and its sprouting pattern), agricultural practices (irrigation, fertilization, and pruning practices) [5], regional and local climatic conditions, and some ecological factors like the activity of aphids' natural enemies work in an integrated manner, resulting in a certain degree of damage [4]. Under favorable conditions, high aphid density may cause a reduction in fruit production by more than 50%, as previously reported for Aphis gossypii [6].…”
Section: Introductionmentioning
confidence: 99%
“…In practice, it is also particularly difficult to protect flush (i.e., young) leaf tissue favoured by psyllids and implicated in transmission (Cifuentes-Arenas et al, 2018), since the most commercially attractive (i.e., cheapest) insecticides are not systemic and do not cover rapidly growing tissue. However, controlling flushing frequency via selective pruning might provide partial mitigation (Matias et al, 2023).…”
Section: Discussionmentioning
confidence: 99%